Sociétés d’accueil et de teranga - Audrey Small (Francosphères)
Throughout his career the sociologist Abdelmalek Sayad argued that emigration and immigration are interdependent. He warns against media and political representations of migration which focus solely on the country of arrival and thus make it more difficult for us to understand the ‘double’ nature of migration. In this article we explore the epistemological and political dangers analysed by Sayad (an ‘ethnocentric’ notion of immigration) and by Anne McClintock (a ‘eurocentric’ idea of the postcolonial) through a reading of three texts by the Senegalese writer Fatou Diome. This approach allows a better understanding of certain aspects of migration rarely discussed in the press and in political discourse in Europe, while also showing that processes of myth-making about migration persist on all sides.